Comparative study of single‐layer graphene and single‐walled carbon nanotube‐filled epoxy nanocomposites based on mechanical and thermal properties. (27th December 2018) - Zakaria, Muhammad Razlan; Abdul Kudus, Muhammad Helmi; Md Akil, Hazizan; Thirmizir, Mohd Zharif Mohd; Abdul Malik, Muhammad Fadhirul Izwan; Othman, Muhammad Bisyrul Hafi; Ullah, Faheem; Javed, Fatima
Abstract : Single layer graphene (SLG) and single‐walled carbon nanotube (SWCNT) were chosen as a candidate to reinforce epoxy resin due to their extraordinary intrinsic properties. In this paper, the comparison of SLG and SWCNT on epoxy nanocomposites has been investigated based on their mechanical and thermal properties. First, the SLG and SWCNT were characterized by extreme high‐resolution field emission scanning electron microscope, high‐resolution transmission electron microscope, Raman spectroscopy, and Fourier transform infrared spectroscopy. The mechanical and thermal properties of both epoxy nanocomposites were investigated at different weight percentages of filler loading (i.e., 0.1–0.5%). The results indicated that the SWCNT‐filled epoxy nanocomposites have higher mechanical properties, but slightly lower thermal properties as compared with the SLG filled epoxy nanocomposites. The tensile strength, fracture toughness and thermal conductivity of the SLG filled epoxy nanocomposites improved up to 7, 14, and 35%, respectively, and the SWCNT filled epoxy nanocomposites improved up to 10, 21, and 26%, respectively. POLYM. COMPOS., 40:E1840–E1849, 2019. © 2018 Society of Plastics Engineers